The Influence of Mobile Information Systems Implementation on Enhancing Human Resource Performance Skills: An Applied Study in a Small Organization - Shakir, Mohanaad; Al Farsi, Maryam Juma; Al-Shamsi, Ibrahim Rashid; Shannaq, Boumedyen; Ghilan Al-Madhagy, Taufiq-Hail (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The human resources mobile information system (HRMoIS) provides users with direct access to information via mobile devices, enhancing efficiency, productivity, and the user experience. It includes mobile applications, websites, SMS services, and other communication mediums. This system enhances information mobility, facilitates operational processes, and supports decision-making in the ever-evolving technological landscape, ultimately improving users’ efficiency and productivity. Al-Anbar Province is undergoing significant urban and economic development. Still, more research is needed on the impact of HRMoIS on employee performance in Anbar to enhance their skills. This study aims to provide insights for top management and decision-makers on implementing similar methods to enhance employee performance. The study employs a questionnaire to survey managers and regular employees in 20 small organizations in Al Anbar, Iraq. The data is analyzed using percentages, frequencies, Pearson correlation, and Cronbach’s alpha coefficient. This allows for a comprehensive examination of all the essential aspects of human resource dynamics. The questionnaire upholds integrity and precision by aligning with roles and responsibilities. The study found that organizations implementing HRMoIS had higher mean values despite barriers such as organizational resistance, limited resources, and inadequate training. The results underscore the importance of organizations addressing these issues and enhancing their HRMoIS adoption. The study investigates the impact of HRMoIS on HR performance in small organizations in Iraq. The results show a positive correlation between mobile information systems and HR management efficiency. The study recommends implementing mobile information systems in small organizations in Al Anbar to enhance their performance. It emphasizes the need for providing necessary hardware and software, hiring experienced consultants, ensuring employee training and development, supplying HRMoIS with relevant data, and appointing experienced employees to keep up with technological advancements.